Multiple-input Single-output Voltage-mode Universal Biquadratic Filter Uisng URC and CCCDBA - Sorapong Wachirarattanapornkul (My University, 2013)
In this paper, a new three-input single-output voltage-mode universal biquadratic filter using two uniformly distributed RC (URC) and current-controlled current differencing buffered amplifier (CCCDBA) are presented.The proposed circuit can realize to low-pass (LPF), high-pass (HPF), band-pass (BPF) and band-stop (BSF) biquadratic functions and provided independent electronic tuning of the natural angular frequency, the quality of the CCCDBA.The proposed circuits have active and passive sensitivities are low and suitability to integrated circuit implementation.The characteristic of the proposed universal biquadratic filter circuit are simulation using PSPICE that confirm the theoretical prediction are also given and discussed Keywordst-voltage-mode circuit, biquad filter, URC and CCCDBA I.
Keywords: Digital biquad filter; Analog and Mixed-Signal Circuit Design